2012
DOI: 10.1186/2046-9063-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular taxonomy of Dunaliella (Chlorophyceae), with a special focus on D. salina: ITS2 sequences revisited with an extensive geographical sampling

Abstract: We used an ITS2 primary and secondary structure and Compensatory Base Changes (CBCs) analyses on new French and Spanish Dunallela salina strains to investigate their phylogenetic position and taxonomic status within the genus Dunaliella. Our analyses show a great diversity within D. salina (with only some clades not statistically supported) and reveal considerable genetic diversity and structure within Dunaliella, although the CBC analysis did not bolster the existence of different biological groups within thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 39 publications
9
36
1
Order By: Relevance
“…, , Assunção et al. ). In particular, it was demonstrated that the CBCs are not diagnostic at the species level and that even genera, families, and orders of green algae can lack CBCs in such regions (Caisová et al.…”
Section: Discussionmentioning
confidence: 99%
“…, , Assunção et al. ). In particular, it was demonstrated that the CBCs are not diagnostic at the species level and that even genera, families, and orders of green algae can lack CBCs in such regions (Caisová et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dunaliella parva UTEX 1983, which aligns in the D. viridis clade (Assunção et al. 2012a), falls within a diverse group of Chlorophyceae containing polyphyletic sarcinoid taxa (Watanabe et al. ), thus it is not surprising that this morphology would be common in Dunaliella .…”
Section: Discussionmentioning
confidence: 99%
“…Two contractile vacuoles are located near the base of the flagella except for the saline and marine species, which lack contractile vacuoles. Saline and marine species, including type species (D. salina), are related to Dunaliellinia, but a freshwater species (D. lateralis) is related to Oogamochlamydinia (Nakada et al, 2008a;Assunção et al, 2012). A pyrenoid is absent or present.…”
Section: Chlainomonas Christen (Not Pictured)mentioning
confidence: 99%